Marketing Strategy Management in Increasing the Marketability of MSME Products in Facing Market Competition - Karollah, Banta; Muhammad; Kurniasih, Nia; Tasrif, Mohammad Jon (Jurnal EMT KITA, 2024)
Micro, small, and medium enterprises (MSMEs) are fundamental components of robust economic resilience, as demonstrated by their persistent operation during Indonesia's monetary crisis, a consequence of the global financial downturn. In contrast, numerous large-scale corporations have experienced insolvency. Consequently, there was a significant wave of employment termination in 1998. Formulating a marketing strategy is critical to securing a sustainable competitive advantage for product- and service-oriented enterprises. A marketing strategy is a foundational element in developing a comprehensive corporate plan. Considering the complexity of challenges faced by enterprises, there exists a necessity for a holistic approach to serve as a framework guiding the organizational segment in executing its operations. Furthermore, the significance of marketing strategies is underscored by the intensifying competition prevalent among businesses in general. This study is motivated by fostering the growth of MSMEs within Mataram, which is characterized by a distinctive array of cultural traditions and a promising national market. This research aims to evaluate the management of marketing strategies aimed at enhancing the marketability of traditional MSME products in Mataram City. The study was carried out in the urban setting of Mataram. The methodologies employed for data collection include documentation, interviews, and observations, constituting a form of descriptive research. The analysis of the effectiveness of marketing strategies reveals a year-on-year increase in overall sales, which serves as a benchmark for assessing the efficacy of marketing strategies amid competition among batik enterprises.